An Original Valveless Artificial Heart Providing Pulsatile Flow Tested in Mock Circulatory Loops. Issue 12 (December 2017) - Tozzi, Piergiorgio; Maertens, Audrey; Emery, Jonathan; Joseph, Samuel; Kirsch, Matthias; Avellan, François
Purpose: We present the test bench results of a valveless total artificial heart that is potentially compatible with the pediatric population. Methods: The RollingHeart is a valveless volumetric pump generating pulsatile flow. It consists of a single spherical cavity divided into 4 chambers by 2 rotating disks. The combined rotations of both disks produce changes in the volumes of the 4 cavities (suction and ejection). The blood enters/exits the spherical cavity through 4 openings that are symmetrical to the fixed rotation axis of the first disk. Mock circulatory system: The device pumps a 37% glycerin solution through 2 parallel circuits, simulating the pulmonary and systemic circulations. Flow rates are acquired with a magnetic inductive flowmeter, while pressure sensors collect pressure in the left and right outflow and inflow tracts. In vitro test protocol: The pump is run at speeds ranging from 20 to 180 ejections per minute. The waveform of the pressure generated at the inflow and outflow of the 4 chambers and the flow rate in the systemic circulation are measured. Results: At an ejection rate of 178 min −1, the Rolling Heart pumps 5.3 L/min for a systemic maximal pressure gradient of 174 mmHg and a pulmonary maximal pressure gradient of 75 mmHg. The power input was 14 W, corresponding to an efficiency of 21%. Conclusions: The Rolling Heart represents a new approach in the domain of total artificial heart. This preliminary study endorses the feasibility of a single valveless device acting as a total artificial heart.